A modern paleolit étrend és az új csodanövénye a földi mandula - Panyor, Ágota; Rabb, Mercédesz (Jelenkori Társadalmi és Gazdasági Folyamatok, 2017)
The healthy nutrition is essential for the subsistence of people. It is everyone because it is part of our daily routine and it is timeless. The main aim of our research was to represent the Palaeolithic lifestyle and to introduce the ground almond and to highlight the multiple use of this plant. In addition to this to find out if the domestic representatives of the Palaeolithic lifestyle heard about it and which form they use it.